2018
DOI: 10.1155/2018/4073963
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Simple Mechanical Analogy to Analytically Tune the PD Controller of a Flexible Manipulator System

Abstract: A study is presented in this paper that uses a simple mechanical analogy to analytically tune the PD (proportional-derivative) controller of a linear flexible manipulator system. More specifically, the aim is to give simple closed-form solutions of the optimal P and D gains to yield the maximum bandwidth under a given damping requirement or conversely the maximum damping under a given bandwidth requirement. The idea of this study is based on the observation that the performance of the complete manipulator syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, manipulators with two or more links were also analyzed employing the FE method [20,21]. An important purpose of dynamical analysis of flexible manipulators is to suppress the vibration of flexible structures [22,23]. Many studies showed that the control schemes were effective for vibration control of flexible manipulators.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, manipulators with two or more links were also analyzed employing the FE method [20,21]. An important purpose of dynamical analysis of flexible manipulators is to suppress the vibration of flexible structures [22,23]. Many studies showed that the control schemes were effective for vibration control of flexible manipulators.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that, in recent years, though there have been several studies related to the flexible manipulators, a few attempts focus on the inverse dynamic analysis for the flexible robots, especially the flexible robots with the translational joints. Most of the works only take into account the revolute joints [17][18][19][20][21][22][23][24][25][26][27][28] when considering the dynamic modeling and analysis of a flexible robot. The large deformation of a flexible link was studied by Celentano.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20]23 Also, the control issues were addressed in the recent works. [24][25][26][27][28] In the literature, the inverse dynamic analysis for flexible robots has been studied by a number of authors. Kwon and Book 29 used AMM for the modeling of the linear inverse dynamics of a single flexible link robot with one rotational joint.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic manipulators are widely used in environments that are hazardous to humans and in situations where there are substantial amounts of repetitive work to reduce the burden on humans and to assist in accomplishing special tasks. To ensure sufficient positioning accuracy at the end of a manipulator, the links of the manipulator can generally be stiffened by a bulky structure to prevent the links from vibrating and to avoid elastic deflection during operation [1][2][3][4]. However, heavy links limit the speed of the manipulator's movement and consume excessive amounts of energy.…”
Section: Introductionmentioning
confidence: 99%